Comparison of the Efficacy of Daily and Weekly Oral Alendronate Treatment in Patients with Secondary Osteoporosis - Sezer Acar; Ahu Paketçi; Korcan Demir; Ece Böber; Ayhan Abacı (Galenos Publishing House, 2019)
INTRODUCTION: The use of alendronate, one of the bisphosphonates that can be used orally in the treatment of osteoporosis, has become widespread in recent years. In this study, we aimed to compare the efficacy of these two different treatment regimens such as weekly and daily oral alendronate in patients with secondary osteoporosis. METHODS: Twenty-eight children and adolescent who were treated with oral daily or weekly alendronate due to secondary osteoporosis were included in this study. Clinical and laboratory features, bone mineral density (BMD) measurements of cases were recorded from file records. RESULTS: This study included 28 children who were diagnosed with secondary osteoporosis due to various chronic diseases and who received weekly (n = 15) or daily (n = 13) alendronate. BMD z-score increased from -3.41 +- 0.50 to -0.50 +- 0.67 in the group receiving daily treatment (p < 0.001) and BMD z-score increased from -3.03 +- 0.86 to -0.22 +- 0.62 in the group receiving weekly treatment (p < 0.001). In both groups, the increase in BMD z-score and the percentage increase in density in g / cm2 were similar (p = 0.490 and p = 0.271). DISCUSSION AND CONCLUSION: This study demonstrated that both weekly and daily single dose of oral alendronate treatment provide similar and significant improvement on BMD. Daily or weekly alendronate treatment regimens can be used effectively and reliably in the treatment of secondary osteoporosis.